Wavelength-tunable passively mode-locked mid-infrared Er3+-doped ZBLAN fiber laser. Issue 1 (December 2017) - Shen, Yanlong; Wang, Yishan; Chen, Hongwei; Luan, Kunpeng; Tao, Mengmeng; Si, Jinhai
Abstract A passively mode-locked Er3+ -doped ZBLAN fiber laser around 3 μm with a wide wavelength tuning range is proposed and demonstrated. The laser cavity was comprised of a semiconductor saturable absorber mirror and a blazed grating to provide a wavelength tunable feedback. The central wavelength of the mode-locked fiber laser can be continuously tuned from 2710 to 2820 nm. The pulse train had a maximum average power of higher than 203 mW, a repetition rate of 28.9 MHz and a pulse duration of 6.4 ps, yielding a peak power of exceeding 1.1 kW. To the best of our knowledge, this is the first demonstration of a wavelength-tunable passively mode-locked mid-infrared fiber laser at 3 μm.